Caracterização da diversidade e estrutura genética de uma população invasora e investigação de possíveis híbridos entre as espécies ameaçadas Leontopithecus rosalia e Leontopithecus chrysomelas - Aliaga Samanez, Gabriela Guadalupe (Universidade Federal de São Carlos, 2022)
The introduction of non-native species is an event that can jeopardize the conservation of native species. The introduction of alien species is usually based on a few individuals and is linked to impacts related to the founder effect and the loss of genetic diversity, which is dependent on the initial effective population size, the population growth rate, and the characteristics of the new colonized environment, which may or may not provide adaptation to it. Invasive species can also favor hybridization with native species, when both species meet and manage to mate, which can be detrimental to biodiversity when one or both pure progenitor strains or species become extinct. The creation of contact zones between species that do not naturally co-occur can therefore pose a pressing threat to biological conservation. This is the case of a specific region of Serra da Tiririca State Park, located in the municipality of Niterói, Rio de Janeiro (RJ), where two pairs of the threatened species Leontopithecus chrysomelas (the golden headed lion tamarin, GHLT, endemic to the Atlantic Forest of Bahia) and a pair of Leontopithecus rosalia (the golden lion tamarin, GLT, endemic to the Atlantic Forest of Rio de Janeiro) were released in the 1990s. Due to the favourable conditions present in this area, these animals were able to adapt and reproduce successfully, generating a new population outside the natural range of L. chrysomelas. Over two decades, this population increased its density exponentially, and it was estimated that there were about 200 individuals, with phenotype of L. chrysomelas in that area in 2009, no individuals with the phenotype of L. rosalia were observed. In view of this event, and the fact that at that time there was only the suspicion of a possible illegal introduction of L. chrysomelas into the Niteroi region, an alternative measure to contain the growth and advance of this population to adjacent areas of natural occurrence of L. rosalia, was to carry out the translocation of individuals with phenotype similar of L. chrysomelas to a fragment of Atlantic Forest, located on the RPPN (Private Natural Heritage Reserve) Veracel Celulose in Belmonte, Bahia. In 2015, however, the illegal introduction of L. chrysomelas and also L. rosalia was confirmed. Although these individuals had the phenotype of L. chrysomelas, it is known that hybrids, besides having phenotypes intermediate to the inter-crossing species, can be more similar to only one of the parental species. Considering that both L. rosalia and L. chrysomelas are species classified by the IUCN as "endangered", investigating the existence of hybrids in this population and characterizing their genetic diversity and structure is relevant for appropriate management measures in regions where currently there are descendants of this population. In this context, the main objective of this study was to carry out genomic and genetic analyses to investigate the occurrence of hybridization and to characterize the genetic diversity and structure of this population. The data showed no signs of hybridization in the Niteroi population, confirming that the individuals are from the species L. chrysomelas. Additionally, genetic diversity values were comparable to those observed for other Leontopithecus populations, showing the absence of negative founder effect consequences and the excellent capacity of the species to re-establish its diversity in the Niteroi region. These findings are relevant to adequately manage individuals from the invasive population and for the conservation programs of both pure species.
Caracterización de la diversidad y estructura genética de una población invasora e investigación de posibles híbridos entre las especies amenazadas Leontopithecus rosalia y Leontopithecus chrysomelas
Keywords: População invasora; Leontopithecus; Hibridização; CIENCIAS BIOLOGICAS::GENETICA